2018
DOI: 10.1111/tpj.14173
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA33732‐respiratory burst oxidase module associated with WRKY1 in tomato‐ Phytophthora infestans interactions

Abstract: Our previous studies indicated that tomato WRKY1 transcription factor acts as a positive regulator during tomato resistance to Phytophthora infestans. However, the molecular mechanism of WRKY1-mediated resistance regulation remains unclear. Here, we used a comparative transcriptome analysis between wild-type and WRKY1-overexpressing tomato plants to identify differentially expressed genes (DEGs) and long noncoding RNAs (DELs), and we examined long non-coding RNA (lncRNA)-gene networks. The promoter sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 89 publications
(101 reference statements)
0
74
0
Order By: Relevance
“…Thus, a gene suppression assay of MSTRG.139242.1 and TEA027212.1 (Ca 2+ -transporting ATPase 13) using AsODNs was conducted and suggested that lncRNA MSTRG.139242.1 may be regulated by its nearby coding gene, TEA027212.1. In a previous study, the tomato lncRNA lncRNA33732 activated by WRKY1 induces RBOH expression and conferred resistance to Phytophthora infestans infection (Cui et al, 2018). In this study, we can speculate that lncRNA MSTRG.139242.1 may interact with its nearby mRNA TEA027212.1 in response to salt stress.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, a gene suppression assay of MSTRG.139242.1 and TEA027212.1 (Ca 2+ -transporting ATPase 13) using AsODNs was conducted and suggested that lncRNA MSTRG.139242.1 may be regulated by its nearby coding gene, TEA027212.1. In a previous study, the tomato lncRNA lncRNA33732 activated by WRKY1 induces RBOH expression and conferred resistance to Phytophthora infestans infection (Cui et al, 2018). In this study, we can speculate that lncRNA MSTRG.139242.1 may interact with its nearby mRNA TEA027212.1 in response to salt stress.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies in plants have found that lncRNAs may co-express with nearby coding genes, thereby regulating the downstream targets of the coding genes and exerting biological functions (Cui et al, 2017(Cui et al, , 2018. Interestingly, in this study, 42 differentially expressed coding genes spaced less than 100 kb away from 35 DE-lncRNAs were identified ( Figure 6 and Supplementary Data Sheet S1: Table S3).…”
Section: Interactions Of De-lncrnas With Mrnasmentioning
confidence: 66%
“…Wang [41] reported the expression and evolution of lncRNAs in Solanaceae. Cui's [42] results provided insights into the WRKY1 − lncRNA33732 − RBOH module involved in the regulation of H 2 O 2 accumulation and resistance to pathogens in tomato. Wang [43] identified several lnRNAs that are involved in TYLCV infection by virus-induced gene silencing (VIGS) and genome-wide analysis.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can execute their biological functions in various ways, e.g., they can regulate the expression of genes either in cis-or trans-acting through sequence complementarity with DNAs or RNAs, epigenetic modification, and promoter activity regulation [1,4]. In cisregulation, a flowering time associated lncRNA (MAS) positively regulated the transcription of MAF4 by interacting with WDR5a, a key element of COMPASS-like complexes [5]; lncRNA33732, which was activated by WRKY1 and located 1.8 kb downstream of RBOH, prompted the transcription of RBOH to increase H 2 O 2 content in tomato defense responses [6]. In transregulation, nitrogen-responsive lncRNA TAS3 regulated the expression of NRT2.4 to affect root development under low-nitrogen condition [7].…”
Section: Introductionmentioning
confidence: 99%